Rare diseases: What information is available on social media? - Lima, Brenda de Oliveira; Luz, Kelly Cristina Suzue Iamaguchi; Sanguino, Gabriel Zanin; Frez , Flávia Cristina Vieira; Lima , Ana Luísa Serrano; Fernandes, Maria Eduarda Itikawa; Rampani, Edicleia Martins; Frez , Fábio Luiz Vieira; Iamaguchi, Franciele Emily; Felipin, Larissa Carolina Segantini (Seven Editora, 2023)
Rare diseases are those that affect up to 65 people per 100,000 individuals, that is, 1.3 people per 2,000 individuals, and are classified in their nature as: genetic and non-genetic in origin. Considering the difficult access to the correct diagnosis and treatment of rare diseases, the internet, through virtual social media, has been a tool for support and clarification of patients and families. The aim of this study was to verify the information available on rare diseases on the internet, using the virtual social media Facebook and Instagram and to evaluate the quantity and relevance of the published material. This is a cross-sectional, descriptive study, using social media Facebook and Instagram, data collection took place from September 7 to November 10, 2022, and this period was established for convenience. For research on social media, the words "rare diseases" were used; "rare diseases in Brazil" and the question: "What are rare diseases?". In the search carried out in the virtual social networks, profiles of support groups and associations with individuals with rare diseases (04), profiles that presented concepts and clarification about rare diseases (04), profiles that disseminated the laws of support for patients with rare diseases (04) and content producers (04) were identified. Virtual social networks are tools used on the internet, being useful and easy to access and with thousands of simultaneous accesses worldwide and with a wide range of information being shared every second. Unfortunately, on the other hand, it is observed that the publications are lacking in depth and, at times, in content quality. While there are pages and profiles dedicated to rare diseases, the vast potential of this digital environment remains underutilized. DOI:https://doi.org/10.56238/sevened2023.004-008